2022
DOI: 10.1200/jco.2022.40.16_suppl.tps619
|View full text |Cite
|
Sign up to set email alerts
|

PARTNER: A randomized, phase II/III trial to evaluate the safety and efficacy of the addition of olaparib to platinum-based neoadjuvant chemotherapy in patients with triple-negative and/or germline BRCA-mutated breast cancer.

Abstract: TPS619 Background: Triple negative breast cancers (TNBCs) are a biologically diverse and aggressive subgroup lacking targeted therapy. TNBC and germline BRCA (gBRCA) breast cancer share certain phenotypic and molecular similarities, with gBRCA mutations seen in 10% to 20% of TNBC patients. Homologous recombination-deficient tumors, especially those caused by germline or somatic BRCA mutations, are thought to be particularly sensitive to PARP inhibitors. Methods: This is a 3-stage open-label randomized phase I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Notably, the PARTNER study (NCT03150576) is a randomized phase II/III study evaluating the addition of olaparib to platinum-based neoadjuvant chemotherapy in patients with TNBC and/or germline BRCA -mutated breast cancer ( N = 756) and pCR as the primary endpoint. 36 In addition, following FDA approval of pembrolizumab plus platinum-containing neoadjuvant chemotherapy as a standard of care for patients with TNBC, 37 further investigation of PARP inhibitors with immunotherapy is in progress for patients with TNBC (talazoparib plus avelumab, NCT03330405; olaparib plus durvalumab, NCT03544125 and NCT03740893; niraparib plus ­dostarlimab, NCT04837209).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the PARTNER study (NCT03150576) is a randomized phase II/III study evaluating the addition of olaparib to platinum-based neoadjuvant chemotherapy in patients with TNBC and/or germline BRCA -mutated breast cancer ( N = 756) and pCR as the primary endpoint. 36 In addition, following FDA approval of pembrolizumab plus platinum-containing neoadjuvant chemotherapy as a standard of care for patients with TNBC, 37 further investigation of PARP inhibitors with immunotherapy is in progress for patients with TNBC (talazoparib plus avelumab, NCT03330405; olaparib plus durvalumab, NCT03544125 and NCT03740893; niraparib plus ­dostarlimab, NCT04837209).…”
Section: Discussionmentioning
confidence: 99%
“…Some trials indicated that PARPi treatment may be improved by addition of ATRi [168,169]. That being the case, many up-to-date studies suggest that PARPi as single agents or in combination with particular compounds can be sufficiently effective against a wider variety of tumors than was thought before.…”
Section: Parp Inhibitorsmentioning
confidence: 99%